Factors blocking the development of north – central Rzeszów - Rybka Adam; Mazur Rafał (Selected Scientific Papers: Journal of Civil Engineering, 2017)
Rzeszów is one of the best developing cities in Poland. Once the small HQ of a principality - due to complicated historical conditioning - it has now become a place where an increasing number of people choose to live. The city with its bursting life, streets and squares starts and ends, however, in an area which only a few dozen years ago still catered for one fifth of the current population. The main reason for this phenomenon is the presence of spatial barriers, which significantly limit the development of the central urban area. This article analyzes the elements, which block the development of the north-central part of Rzeszów. An appropriate diagnosis of the problem may in the future allow the right actions in urban planning to be taken in order to cross these barriers. This may lead to the future development of areas with huge urbanization potential. Investments undertaken by city authorities to develop the northern peripheries of Rzeszów may trigger the development of the central district in this direction. This may occur as a result of concrete design interventions. The new part of the central district should have the scale and proportions of urban space that answer to the needs of a dynamically developing capital of the Podkarpacie region.